Measuring The Determinants of Earnings Management - Ardiani Ika Sulistyawati; Aprih Santoso; Arief Himmawan Dwi Nugroho (Quantitative Economics and Management Studies, 2022)
The purpose of this research is to investigate the impact of profitability, leverage, deferred tax expense, tax planning on earnings management. The research sample consisted of 12 manufacturing companies on the IDX for the period 2018 - 2020. Data on the company's annual financial statements, 33 data were obtained which were analyzed before outliers, and 26 data were analyzed after outliers. Methods of data analysis using classical assumption test, hypothesis testing and multiple linear regression. The research results show that profitability has a significant positive effect, deferred tax expense has a significant negative effect, leverage and tax planning have no significant effect on earnings management